The Last of Us? Czy istnieje przyszłość dla neofilologii? - Grabowska, Monika; Smuk, Maciej; Sowa, Magdalena (Neofilolog, 2024)
The article is about philological studies in Poland. It discusses the results of a survey conducted at 43 programs at philological studies in 13 Polish universities, with the aim of outlining the profile of students starting their studies (first year of bachelor’s and master’s programs) and those completing them (final year of bachelor’s and master’s programs). In the first case, the goal was to understand the motivations for pursuing studies and the expectations associated with them. In the second case, the objective was to determine the level of satisfaction with the completed studies and the reasons for satisfaction or dissatisfaction. In total, nearly 5000 respondents participated in the study. The results allowed us to draw conclusions regarding the profile of contemporary students of foreign philology and to propose some directions in which the programs might evolve.